RANKL expressed on synovial fibroblasts is primarily responsible for bone erosions during joint inflammation. Issue 6 (29th May 2015) - Danks, Lynett; Komatsu, Noriko; Guerrini, Matteo M; Sawa, Shinichiro; Armaka, Marietta; Kollias, George; Nakashima, Tomoki; Takayanagi, Hiroshi
Abstract : Objective: RANKL is mainly expressed by synovial fibroblasts and T cells within the joints of rheumatoid arthritis patients. The relative importance of RANKL expression by these cell types for the formation of bone erosions is unclear. We therefore aimed to quantify the contribution of RANKL by each cell type to osteoclast differentiation and bone destruction during inflammatory arthritis. Methods: RANKL was specifically deleted in T cells ( Tnfsf11 flox/Δ Lck -Cre), in collagen VI expressing cells including synovial fibroblasts ( Tnfsf11 flox/Δ Col6a1 -Cre) and in collagen II expressing cells including articular chondrocytes ( Tnfsf11 flox/Δ Col2a1 -Cre). Erosive disease was induced using the collagen antibody-induced arthritis (CAIA) and collagen-induced arthritis (CIA) models. Osteoclasts and cartilage degradation were assessed by histology and bone erosions were assessed by micro-CT. Results: The inflammatory joint score during CAIA was equivalent in all mice regardless of cell-targeted deletion of RANKL. Significant increases in osteoclast numbers and bone erosions were observed in both the Tnfsf11 flox/Δ and the Tnfsf11 flox/Δ Lck -Cre groups during CAIA; however, the Tnfsf11 flox/Δ Col6a1 -Cre mice showed significant protection against osteoclast formation and bone erosions. Similar results on osteoclast formation and bone erosions were obtained in CIA mice. The deletion of RANKL on any cell type did not prevent articular cartilage loss in either model of arthritis used. Conclusions: The expression of RANKL on synovial fibroblasts rather than T cells is predominantly responsible for the formation of osteoclasts and erosions during inflammatory arthritis. Synovial fibroblasts would be the best direct target in RANKL inhibition therapies.